Influence of collisions on ion dynamics in the inner comae of four comets - Mandt,KE; Eriksson,A; Beth,A; Galand,M; Vigren,E (ASTRONOMY & ASTROPHYSICS, 2019)
Context. Collisions between cometary neutrals in the inner coma of a comet and cometary ions that have been picked up into the solar wind flow and return to the coma lead to the formation of a broad inner boundary known as a collisionopause. This boundary is produced by a combination of charge transfer and chemical reactions, both of which are important at the location of the collisionopause boundary. Four spacecraft measured ion densities and velocities in the inner region of comets, exploring the part of the coma where an ion-neutral collisionopause boundary is expected to form.Aims. The aims are to determine the dominant physics behind the formation of the ion-neutral collisionopause and to evaluate where this boundary has been observed by spacecraft.Methods. We evaluated observations from three spacecraft at four different comets to determine if a collisionopause boundary was observed based on the reported ion velocities. We compared the measured location of the ion-neutral collisionopause with measurements of the collision cross sections to evaluate whether chemistry or charge exchange are more important at the location where the collisionopause is observed.Results. Based on measurements of the cross sections for charge transfer and for chemical reactions, the boundary observed by Rosetta appears to be the location where chemistry becomes the more probable result of a collision between H2O and H2O+ than charge exchange. Comparisons with ion observations made by Deep Space 1 at 19P/Borrelly and Giotto at 1P/Halley and 26P/Grigg-Skjellerup show that similar boundaries were observed at 19P/Borrelly and 1P/Halley. The ion composition measurements made by Giotto at Halley confirm that chemistry becomes more important inside of this boundary and that electron-ion dissociative recombination is a driver for the reported ion pileup boundary.